Memahami Manajemen Alih Tangan Kasus - Siti Dwi Yasinta; Bakhrudin All Habsy; Fhito Atma Kumariaksy; Fanzha Erza Nanda Saputra; Musyaffa Dafa Firdaus; Annur Rizqiah Putri Wijaya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Case transfer in management Guidance and counseling is an important process in handling student problems that are too complex. The purpose of this case transfer was to obtain supporting data regarding the students who were transferred to the case and to provide more effective guidance services by experts. This process involves identification, assessment, and transfer of responsibility from one counselor to another counselor or the BK team. For example, a psychological test, a guidance and counseling teacher can collaborate with a psychology institution to obtain data related to students' psychological development. The case transfer program can collaborate with other professionals, such as psychiatrists, police, doctors and other professionals.